Anomalous left pulmonary artery: case reports exploring anatomic variants - Yibei Zhu; Olivia McCloskey; Justin A. Robinson; Robert D. Stewart; Chandrakant R. Patel; Kristen Breedlove; Tara Karamlou (Journal of Cardiothoracic Surgery)
Abstract Background Pulmonary artery sling (PAS) is a rare congenital anomaly where the left pulmonary artery (LPA) branches from the right pulmonary artery, compressing the trachea and esophagus and frequently leading to respiratory distress in infants. Surgical intervention, such as LPA reimplantation or translocation, is crucial to relieve airway compression and restore normal pulmonary function. Case presentation This report highlights varied LPA anatomies, including a unique case of an anomalous LPA without true sling formation but causing tracheal compression, alongside two typical PAS cases. Respiratory symptoms were successfully mitigated in all three cases without concomitant tracheal reconstruction. Conclusions This report underscores the necessity of thorough preoperative assessment of airway anatomy and highlight the importance of individualized surgical planning for anomalous LPA.